Agent-based modeling and simulation in architecture - Stieler, David; Schwinn, Tobias; Leder, Samuel; Maierhofer, Mathias; Kannenberg, Fabian; Menges, Achim (Automation in construction, 2022)
Over the last two decades, the use of agent-based models (ABMs) to model and simulate the dynamics of complex systems has increased significantly among various scientific fields, including architecture. Based on a systematic literature review, this paper presents a classification for agent-based modeling and simulation (ABMS) in architecture based on the individual entities being modeled as agents. The classification is based on a reproducible search method capable of incorporating findings from different domain-specific databases to systematically retrieve relevant literature for ABMS in architecture. Subsequently, in each of the ABMs encountered in the selected literature, we identify what entity an agent in the model represents. Based on this identification, a comprehensive classification for ABMs in architecture is achieved. By describing each of the resulting categories, we provide new insights into the field of ABMS in architecture. Finally, we discuss limitations, as well as future trends and possibilities for ABMS in architecture. [Display omitted] •We present a literature retrieval approach for domain-specific ABMS publications.•Our literature review is based on more than 600 relevant publications.•We propose an agent-centered model classification with 6 categories.•Any model encountered in the review can be classified using only 6 categories.•We identify future trends for each category and for ABMS in architecture in general.